2020
DOI: 10.1073/pnas.1909915117
|View full text |Cite
|
Sign up to set email alerts
|

Brain-wide functional architecture remodeling by alcohol dependence and abstinence

Abstract: Alcohol abuse and alcohol dependence are key factors in the development of alcohol use disorder, which is a pervasive societal problem with substantial economic, medical, and psychiatric consequences. Although our understanding of the neurocircuitry that underlies alcohol use has improved, novel brain regions that are involved in alcohol use and novel biomarkers of alcohol use need to be identified. The present study used a single-cell whole-brain imaging approach to 1) assess whether abstinence from alcohol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 108 publications
5
100
0
Order By: Relevance
“…To further assess the impact of antibiotic treatment on brain networks, we evaluated the degree of associations between changes in neuronal activity (i.e., functional connectivity) in each brain region during oxycodone intoxication and withdrawal (Kimbrough et al, 2020). We found that antibiotic treatment was associated with dysregulation of the functional network that was produced by decorrelations between several brain regions compared with the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…To further assess the impact of antibiotic treatment on brain networks, we evaluated the degree of associations between changes in neuronal activity (i.e., functional connectivity) in each brain region during oxycodone intoxication and withdrawal (Kimbrough et al, 2020). We found that antibiotic treatment was associated with dysregulation of the functional network that was produced by decorrelations between several brain regions compared with the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…A hub is defined as a node with high connectivity to other nodes in the same module (provincial hubs) or to other modules (connector hubs) [ 191 , 192 ]. Hub brain regions are critical to network function and represent the highest level of connectivity [ 99 , 129 , 171 , 190 , 193 ]. An example of hub identification and validation in brain-wide neural networks can be seen in a study by Vetere et al, in which in silico node deletion and in vivo chemogenetic silencing of the identified nodes confirmed the connection between a region’s node degree and role in memory consolidation [ 129 ].…”
Section: Neural Networkmentioning
confidence: 99%
“…This fear network was further examined using in vivo chemogenetic silencing of different network nodes to confirm the importance of the hubs predicted in network models [ 129 ]. Similarly, an unbiased brain-wide Fos protein approach, using the single-cell whole-brain imaging (iDISCO+) method, has been combined with functional connectivity and graph theory to identify changes to neural network structure and function caused by withdrawal from alcohol and psychostimulants [ 99 , 217 ].…”
Section: Leveraging Neural Network In Preclinical Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations